Navigating a Life-Threatening Airway Emergency: Clinical Diagnosis and Surgical Management of Ludwig's Angina in a Resource-Limited Setting - Adhe Ismunandar; Febriadi Rosmanato; Kenzartang (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Odontogenic abscesses, common in clinical practice, possess the potential to escalate into life-threatening emergencies. The contiguous spread of polymicrobial infections into the deep fascial spaces of the neck can precipitate Ludwig's angina, a rapidly progressive cellulitis of the floor of the mouth characterized by acute airway compromise. This report details the diagnosis and management of such a case, emphasizing the critical role of clinical acumen when gold-standard diagnostic modalities are unavailable. Case presentation: A 43-year-old male presented with a one-week history of progressive, painful swelling of his right mandible, accompanied by fever and trismus. The working diagnosis was Ludwig's angina secondary to an odontogenic abscess originating from the mandibular right second molar (tooth #47). Despite an initial radiological report erroneously noting an issue with tooth #37, all clinical evidence pointed to a right-sided pathology. Diagnosis was established through physical examination and basic radiography, which confirmed significant soft tissue swelling. Management involved immediate surgical incision and drainage under general anesthesia, aggressive intravenous antibiotic therapy, and meticulous postoperative care. The causative tooth was subsequently extracted. The patient experienced a complete resolution of symptoms and a full functional recovery. Conclusion: Ludwig's angina remains a formidable surgical emergency. This case underscores that even with limited diagnostic resources, a decisive diagnosis based on strong clinical findings, followed by prompt and aggressive surgical decompression, is paramount to preventing mortality and ensuring a favorable patient outcome.